R. Evan Ellis, China in Latin America: The Whats and Wherefores, Boulder/Londres, Lynne Rienner, 2009, 329 pp. - Carrillo, Andrés (El Colegio de México, 2011)
R. Evan Ellis, China in Latin America: The Whats and Wherefores, Boulder/London, Lynne Rienner, 2009, 329 pp.